3D printing processes for photocurable polymeric materials: technologies, materials, and future trends. Issue 3 (July 2018) - Taormina, Gabriele; Sciancalepore, Corrado; Messori, Massimo; Bondioli, Federica
The aim of this review is a faithful report of the panorama of solutions adopted to fabricate a component using vat photopolymerization (VP) processes. A general overview on additive manufacturing and on the different technologies available for polymers is given. A comparison between stereolithography and digital light processing is also presented, with attention to different aspects and to the advantages and limitations of both technologies. Afterward, a quick overview of the process parameters is given, with an emphasis on the necessities and the issues associated with the VP process. The materials are then explored, starting from base matrix materials to composites and nanocomposites, with attention to examples of applications and explanations of the main factors involved.